2021
DOI: 10.1021/acsami.1c05769
|View full text |Cite
|
Sign up to set email alerts
|

One-Way Continuous Deposition of Monolayer MXene Nanosheets for the Formation of Two Confronting Transparent Electrodes in Flexible Capacitive Photodetector

Abstract: MXenes based on titanium carbide are promising next-generation transparent electrode materials due to their high metallic conductivity, optical transparency, mechanical flexibility, and abundant hydrophilic surface functionality. MXene electrodes offer a much wider conductive surface coverage than metal nanowires, thereby gaining popularity as flexible electrode materials in supercapacitors and energy devices. However, given that monolayer MXene nanosheets are only a few nanometers thick, meticulous surface tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…[ 33 ] The expansion of the d ‐spacing from 9.26 to 13.93 Å compared to Ti 3 AlC 2 further confirms the complete exfoliation of few‐layered Ti 3 C 2 T x with the presence of surface terminations and water molecules between the MXene layers. [ 34 ] The diffraction peaks (101) and (002) are in good agreement with the tetragonal rutile phase (JCPDS no. 03‐065‐1119, a = 4.5933 Å and c = 2.9592 Å) of TiO 2 .…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…[ 33 ] The expansion of the d ‐spacing from 9.26 to 13.93 Å compared to Ti 3 AlC 2 further confirms the complete exfoliation of few‐layered Ti 3 C 2 T x with the presence of surface terminations and water molecules between the MXene layers. [ 34 ] The diffraction peaks (101) and (002) are in good agreement with the tetragonal rutile phase (JCPDS no. 03‐065‐1119, a = 4.5933 Å and c = 2.9592 Å) of TiO 2 .…”
Section: Resultsmentioning
confidence: 60%
“…[ 33 ] Ti 2p core levels are fitted to five doublets (Ti 2p 3/2 , Ti 2p 1/2 ) located at Ti‐C (454.81, 460.3 eV), Ti 2+ (455.64, 461.11 eV), Ti 3+ (456.82, 461.96 eV), TiO 2 (458.21, 462.92 eV), and C‐Ti‐F x (459.21, 464.4 eV) bonds respectively, which are in agreement with the previously reported XPS results of MXenes with ‐F functional groups. [ 34 ] The Ti 3 C 2 T x MXene nanosheets on glass remain over 90% transmittance ranging from 300 to 850 nm (Figure 1e). The TiO 2 NRs exhibit high absorption in the UV‐A band (Figure 1f).…”
Section: Resultsmentioning
confidence: 99%
“…[ 60 ] Most recently, Kim and co‐workers developed a flexible capacitive photodetector with monolayer 2D MXene as transparent electrodes and the Cu‐doped ZnS semiconductor particles as photoactive materials. [ 56 ] The device exhibited excellent mechanical stability due to the high affinity between the MXene and flexible substrate.…”
Section: Fundamentals Of Flexible Photodetectorsmentioning
confidence: 99%
“…M and X represent transition metal and chalcogen atom, respectively. Since the chalcogen atoms are saturated and the molecular interlayer force of the TMD material is weak, few-layer TMD can be obtained by mechanical exfoliation, vapor deposition methods, etc. Due to the interlayer isolation of TMDs, 2D TMDs exhibit better properties than 3D TMDs, facilitating their potential advantages in electronics, photonics, biomedicine, and sensor. For instance, Avdizhiyan et al created photodetectors (PDs) based on two-dimensional TMD alloys and showed that the spectral sensitivity of the created PDs can be significantly altered by changing the composition of TMD . Zhang et al have demonstrated that monolayer TMD nanosheets (NSs), including MoS 2 , TiS 2 , and TaS 2 , can serve as a sensing platform for DNA fluorescence detection, and they have been successfully used for multiplex detection of DNA …”
Section: Introductionmentioning
confidence: 99%